International Grain Reserves : And Other Instruments to Address Volatility in Grain Markets - Wright, Brian (2012)
In the long view, recent grain price volatility is not anomalous. Wheat, rice, and maize are highly substitutable in the global market for calories, and when aggregate stocks decline to minimal feasible levels, prices become highly sensitive to small shocks, consistent with storage models. In this decade, stocks have declined due to high income growth and biofuels mandates. Recently, shocks including the Australian drought and biofuels demand boosts due to the oil price spike were exacerbated by a sequence of trade restrictions by key exporters beginning in the thin global rice market in the fall of 2007, which turned market anxiety into panic. To protect vulnerable consumers, countries intervened in storage markets and, if they were exporters, to limit trade access. Recognizing these realities, vulnerable countries are building strategic reserves. The associated expense and negative incentive effects can be controlled if reserves have quantitative targets related to the consumption needs of the most vulnerable, with distribution to the latter only in severe emergencies. More-ambitious plans manipulate world prices via buffer stocks or naked short speculation to keep prices consistent with fundamentals. Past interventions of either kind have been expensive, ineffective, and generally short-lived. Further, there is no significant evidence that prices do not reflect fundamentals, including export market access.